Analisis Kebijakan Pilar Konservasi dalam Tata Kelola Kampus Guna Mewujudkan Good Government - Rachmadi, Moch Faizal (JDEP (Jurnal Dinamika Ekonomi Pembangunan), 2019)
The purpose of this study is to analyze and understand the benefits of applying pillars in supporting good governance at Semarang State University. There are 7 types of policies in the approved pillars which are green architecture, paper policies, waste management and many more. With the pillar of this improvement, it makes the campus governance system more effective, efficient and able to increase financial inclusion by taking into account environmental aspects. The method used in this study is a qualitative descriptive analysis method with primary and secondary data for phenomena that occur in the field in explaining the data to support this work. Based on studies conducted, it can be concluded that governance is able to realize governance, better operational management in realizing Semarang State University to be a good government.